Detection of iodixanol-induced allergic reaction signals in Chinese inpatients: a multi-center retrospective database study using prescription sequence symmetry analysis - Zhang, Dandan; Yang, Xinchen; Yang, Zhangwei; Sun, Wei; Chen, Shunjie; Xu, Lingxiao (Frontiers in Pharmacology, 2024)
Objective: This study aimed to explore the signal detection method for allergic reactions induced by inpatient iodixanol injection.A database of 3,719,217 hospitalized patients from 20 large Chinese general hospitals was processed and analyzed using the prescription sequence symmetry analysis (PSSA) method.Results: 126,680 inpatients who used iodixanol and were concurrently treated with antiallergic drugs were analyzed. In the medical records of these patients, only 32 had documented iodixanol allergies. Statistical analysis identified 22 drugs in 4 categoriescalcium preparations, adrenergic/dopaminergic agents, glucocorticoids, and antihistamines -as marker drugs. With time intervals of 3, 7, and 28 days, the adjusted sequence ratios (aSR) for all anti-allergics and the 4 categories were greater than 1. The 7-day aSRs were 2.12 (95% CI: 2.08-2.15), 1.70 (95% CI: 1.68-1.73), 3.85 (95% CI: 3.75-2.30), 2.30 (95% CI: 2.26-2.35), and 1.95 (95% CI: 1.89-2.02), respectively. The proportions of adverse drug events indicated by each signal were: all anti-allergics (2.92-3%), calcium gluconate (0.19-0.52%), adrenergic/dopaminergic agents (2.20-3.37%), glucocorticoids (3.13-3.76%), and antihistamines (1.05-1.32%).This first multi-center Chinese inpatient database study detected iodixanol allergy signals, revealing that reactions may be much higher than collected spontaneous reports. Iodixanol risk exposure was closer to actual pharmaceutical care findings. PSSA application with ≤7 day intervals appears better suited for monitoring late allergic reaction signals with these drugs.